Analisis Kelengkapan Kuantitatif Berkas Resume Medis di Rumah Sakit Angkatan Laut Dr. Ramelan Surabaya - Susanti, Ari; Amalin, Atika Mima; Khoir, Hanna Miftachul; Rosida, Fifin Alfiatur; Chudayfi, Ahmad; Adi, Dominikus Sukma (HB PRESS, 2023)
A complete medical record form is an indicator of good medical record management and directly affects service quality. Analysis of the completeness of medical record files at Dr. Ramelan Surabaya found that the completeness of the medical resume had not reached 100%, only 90% completeness. The purpose of this study was to analyze the completeness of medical resume files at Dr. Ramelan Surabaya with descriptive method. Data collection used the cross sectional method in September 2022 as many as 21 medical resume forms. The results showed that the identification review obtained 100% complete in filling out medical resumes. Completion of medical resumes on critical report reviews is at least 19% on treatment while being treated. Authentication review is only 76% for filling in the patient's full name. Review the documentation that is correct, the blank part is 19%. The conclusion of this study is the highest incompleteness in the treatment while being treated by 81% in the review of important reports, so filling out the medical record file at RSPAL Dr. Ramelan is said to be still incomplete.